Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian - Hidayat, Ridho Rahmad; Rayuwanto, Rayuwanto (Universitas Darwan Ali, 2022)
This thesis presents an investigation of the influence of factors such as price and product quality on consumer decisions regarding the purchase of Kanzler sausages in the city of Sampit. The investigative instrument was compiled in the form of a questionnaire distributed online. In this study, the type of sampling used is convenience sampling because it is a fast, simple, and affordable method, in addition, this approach is efficient in terms of time and money, and the sample uses the simplest and most convenient way for the researcher. Determination of the sample with as many as one hundred respondents, namely the unknown population method. Because of the incentives provided by the very high level of customer purchase, this research was conducted. The purpose of this study was to determine the extent to which Kanzler sausage is influenced by the independent variables, namely price and product quality, and which of the two variables has the greatest influence. The results of multiple regression analysis in this study indicate that price and product quality have a significant and positive effect on purchasing decisions for Kanzler sausage.